Sex difference in circulating soluble form of ACE2 protein in moderate and severe COVID-19 and healthy controls - Robertson, Josefina; Nellgård, Bengt; Hultén, Lillemor Mattsson; Nilsson, Staffan; Dalla, Keti; Börjesson, Mats; Zetterberg, Henrik; Svanvik, Joar; Gisslén, Magnus (Frontiers in Medicine, 2022)
Introduction Membrane-bound angiotensin-converting enzyme-2 (ACE2) in epithelial cells is the main receptor for SARS-CoV-2. The extracellular portion of ACE2 may be shedded to plasma in which process ADAM17 (a disintegrin and metalloproteinase 17) is important. Results on the relationship between circulating levels of the soluble form of ACE2 (sACE2) and disease severity are inconclusive. This study investigates if sACE2 concentration correlates with COVID-19 severity, and whether this is affected by sex. Materials and methods Soluble form of ACE2 was analyzed in three groups: 104 patients (23 women and 81 men) with severe COVID-19 admitted to an intensive care unit (ICU), patients with moderate COVID-19 who required hospital care (n = 19, 4 women and 15 men), and age and sex matched healthy controls (n = 20, 4 women and 16 men). Blood samples were collected at hospital admission between 18 March 2020, and 3 May 2021, and at follow-up between 27 October 2020, and 19 October 2021. Circulating sACE2 (μg/L) was measured in EDTA plasma with a sensitive enzyme-linked immunosorbent assay. Additionally, CRP, ferritin, and lymphocyte count were analyzed during hospital stay. Results In total, 23 patients (22%) died in the ICU. When comparing healthy controls [mean age 58.1 (SD 11.4) years] and patients with moderate COVID-19 [mean age 61.0 (SD 13.2) years] with patients in the ICU [mean age 63.6 (SD 11.6) years], we found that sACE2 concentration decreased (70% reduction) with disease severity in men (p = 0.002) but increased 3.7-fold with severity in women (p = 0.043), suggesting a sex-related difference in how COVID-19 severity is related to sACE2 concentration. Moreover, we identified a relationship between inflammatory biomarkers and sACE2 concentration during the intensive care treatment, such that higher CRP and higher ferritin concentration correlated with lower sACE2 concentration in men. Conclusion The decrease in sACE2 concentration, selectively in men, in severe COVID-19 is of pathophysiological interest since men are affected more severely by the disease compared to women. Additionally, the inflammatory biomarkers, CRP and ferritin, correlated inversely with sACE2 concentration, suggesting a role in severe disease. Our findings imply that sACE2 is a possible biomarker of disease severity in a sex-specific manner.